Effect of Monensin on performance of finishing steers - D. Tobyne; G. Fink; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1977)
We used 72 Hereford and Hereford x Angus cross yearling steers to further evaluate 200 mg Monensin (trade name Rumensin) per head daily. Monensin improved gain 6.7% and significantly improved efficiency, 12.3%.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Monensin; Performance; Steers